Impact of agricultural land use changes on food access in Mwatate Sub-County, Taita Taveta County, Kenya - Bonventure, Obeka Mwanzi; Wacker, Elisabeth; Shauri, Halimu; de Vries, Walter Timo (Frontiers in Sustainable Food Systems, 2025)
IntroductionWhereas Sustainable Development Goal 2 seeks to achieve zero hunger by 2030, food security remains a global challenge. Therefore, SDG 2 aims to achieve sufficient food access through sustainable agriculture. This is in line with the tenets of SDG1 that endeavor to end poverty in its diverse forms and, among other targets, secure land tenure rights. However, disparities in land tenure security still exist, especially in developing societies, and the prevalence of food insecurity is rising. Consequently, this study sought to establish the influence of land use patterns on food security.MethodsA sample of 301 households was selected using proportionate sampling techniques. Accordingly, we used a cross-sectional research design, whereas data was collected using semi-structured interview guides. The Malthusian theory was used as an interpretive theoretical framework for this study.Results and discussionFurthermore, using the Household Food Insecurity Access Scale (HFIAS), it was established that the study site was food insecure, whereby only 22.6% of the households were food secure. Moreover, 39.5% of households experienced severe food insecurity, 16.3% had moderate food access, and 21.3% had mild food security. Results further revealed that agriculture characterized by subsistence farming was the primary land use pattern. Additionally, findings revealed agricultural expansion and increased demand for settlement spaces, resulting in deforestation, clearing of bushes, and general land degradation. Consequently, soil erosion and loss of soil fertility necessitating the use of pesticides and fertilizers were reported. Using a 5% significance level, a chi-square analysis revealed that these land use changes significantly influenced food security. Based on these findings, we recommend adopting sustainable agriculture to boost land productivity and diversify livelihood sources to reduce overreliance on mono-crop subsistence farming. Moreover, we draw the need to increase awareness of environmental conservation through agriculture extension services.